2011
DOI: 10.1111/j.1600-0625.2010.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased retinoid concentration and retinoid signalling pathways in human atopic dermatitis

Abstract: Atopic dermatitis (AD) is one of the most common skin diseases. Various features present in AD like inflammation, reduced apoptosis, altered epidermal differentiation and hyperproliferation as well as permeability dysfunction are also regulated by retinoids. The aim of our study is to identify the retinoid signalling pathways and retinoid concentration profiles in AD skin. Human skin biopsies were obtained from healthy volunteers (HS) (n = 6) and patients with AD (n = 6), with both affected (AS) and non-affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
5
45
1
Order By: Relevance
“…In general, retinoid dysregulation in affected as well as nonaffected AD skin is one main feature of this disease [9]. In our study, thromboxane synthase and thromboxane receptor as well as 5-lipoxygenase and leukotriene B4 receptor [19,20] increased after oral RXR ligand treatment, which concludes that itch and scratch responses, partly responsible for the AD phenotype, are also co-initiated via increased systemic RXR-mediated signaling [37].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In general, retinoid dysregulation in affected as well as nonaffected AD skin is one main feature of this disease [9]. In our study, thromboxane synthase and thromboxane receptor as well as 5-lipoxygenase and leukotriene B4 receptor [19,20] increased after oral RXR ligand treatment, which concludes that itch and scratch responses, partly responsible for the AD phenotype, are also co-initiated via increased systemic RXR-mediated signaling [37].…”
Section: Discussionmentioning
confidence: 67%
“…Dysregulation of retinoid metabolism is either the cause or the initiator of various diseases including allergic diseases [23,24]. Reduced concentrations of ATRA and retinol as well as reduced retinoid signaling are present in affected as well as nonaffected skin of AD patients [9]. In our studies, we observed that systemic treatment of a synthetic RXR ligand leads to reduced retinoid signaling in mouse skin and therefore it might possibly be relevant for reduced retinoid concentrations and retinoid signaling in mouse skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that retinoid signaling, along with the expression of the various target genes involved, is generally much lower in the skin of patients with chronic atopic dermatitis than in that of healthy volunteers (table 2) [73]. Of note is the low expression of retinaldehyde dehydrogenase 1 (RALDH1), the enzyme mainly responsible for ATRA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous features like epidermal permeability [60], epidermal hyperproliferation [61], epidermal differentiation [54,62,63,64], sebum secretion [65], Th1/Th2 balance [52,66,67,68], apoptosis [69], lymphocyte proliferation [70], eosinophilia [71], chemokine secretion [53,72], inflammatory responses [52,67], retinoid signaling [73], thymic stromal lymphopoietin (TSLP) production [53] and bacterial colonization [74] are regulated by RAR and RXR pathways and are also severely dysregulated in atopic dermatitis (table 1). …”
Section: Introductionmentioning
confidence: 99%